DAMPAK INVASI RUSIA KE UKRAINA TERHADAP ABNORMAL RETURN SAHAM EMITEN MIGAS DI BURSA EFEK INDONESIA TAHUN 2022 - Kurniawan, Steven Nathaniel; Sudirman, I Made Surya Negara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023, 2023)
This research is a study that aims to examine whether or not there were significant abnormal returns before and after the Russian invasion of Ukraine on 24 February 2022 for oil & gas issuers on the Indonesia Stock Exchange. Determination of the sample using the purposive sampling method and obtained as many as 28 issuers who are considered feasible to be used as a trial sample. This study uses secondary data in the form of daily stock closing prices. The event period selected in this study is 11 trading days consisting of 5 days before (t-5), the day when the event occurs (t=0) and 5 days after (t+5) the event occurs, namely on February 24, 2022. Hypothesis testing using the one sample t-test. The results of the study show that there are significant differences in the days before and after the Russian invasion of Ukraine in 2022. Thus this event is considered to have information content that causes the capital market to react to it as evidenced by abnormal changes in stock prices.